MATLAB for neuroscientists : an introduction to scientific computing in MATLAB - Wallisch, Pascal, 1978- (Academic Press, 2014)
This title is an introduction to MATLAB, the current standard for scientific computing, written specifically for students and researchers in neuroscience and related fields. It serves as the first comprehensive study manual and teaching resource for the use of MATLAB in the neurosciences and psychology.